Counseling Group With self-management techniques for Lower Prejudice Social Learners - Endang Sri Estimurti; Niky Anita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Service Counseling Group with self-management techniques for Lower Prejudice Social Students at SMAN 2 Palangka Raya. The aim of this study For know service counseling group with deep self-management techniques lower participants ' social prejudices educate. Type of research used is quantitative with Pre- Experiment technique dangn form of One-Group Pretest-Posttest Design. Population in this research is participant educate class X MIPA-7 at SMAN2 Palangka Raya, totaling 40 people, with sample of 9 participants identified students own level high social prejudice. Data is analyzed with the T Test Using SPSS software application version 20.00. technique Data collection uses observation and scale prejudice social. Based on Pre-test results before providing subject treatment get mark average scores were 86-114 in in category high, and after giving treatment based on Subject average Post-test results get mark score 57-85 and in in category currently. On observation beginning before giving treatment mark score 9-13 in in category low and after providing treatment during observation end of subject average get mark score 4-8 in in category low. Research result showing ninth participant students who are given treatment experience decline behavior prejudice social after providing known treatment from results Pretest-Posttest comparison